2007
DOI: 10.1083/jcb.200606027
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell death program leads to neutrophil extracellular traps

Abstract: Neutrophil extracellular traps (NETs) are extracellular structures composed of chromatin and granule proteins that bind and kill microorganisms. We show that upon stimulation, the nuclei of neutrophils lose their shape, and the eu- and heterochromatin homogenize. Later, the nuclear envelope and the granule membranes disintegrate, allowing the mixing of NET components. Finally, the NETs are released as the cell membrane breaks. This cell death process is distinct from apoptosis and necrosis and depends on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

119
2,661
9
31

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 2,685 publications
(2,820 citation statements)
references
References 38 publications
119
2,661
9
31
Order By: Relevance
“…It has been shown that PMA‐induced NETosis is a ROS‐dependent process and is inhibited by the NADPH oxidase inhibitor, DPI 3. After DPI treatment (10 µM, 30 min), SYTOX Green‐positive cells were significantly reduced in comparison with the samples without DPI treatment (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…It has been shown that PMA‐induced NETosis is a ROS‐dependent process and is inhibited by the NADPH oxidase inhibitor, DPI 3. After DPI treatment (10 µM, 30 min), SYTOX Green‐positive cells were significantly reduced in comparison with the samples without DPI treatment (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…NETosis is thought to be distinct from apoptosis or necrosis 3. To determine that SYTOX Green does not recognize apoptotic cells, apoptosis was induced on neutrophils by etoposide.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations